Differential survival throughout the full annual cycle of a migratory bird presents a life‐history trade‐off. Issue 5 (30th March 2021) - Buechley, Evan R.; Oppel, Steffen; Efrat, Ron; Phipps, W. Louis; Carbonell Alanís, Isidoro; Álvarez, Ernesto; Andreotti, Alessandro; Arkumarev, Volen; Berger‐Tal, Oded; Bermejo Bermejo, Ana; Bounas, Anastasios; Ceccolini, Guido; et al.
Abstract: Long‐distance migrations are among the most physically demanding feats animals perform. Understanding the potential costs and benefits of such behaviour is a fundamental question in ecology and evolution. A hypothetical cost of migration should be outweighed by higher productivity and/or higher annual survival, but few studies on migratory species have been able to directly quantify patterns of survival throughout the full annual cycle and across the majority of a species' range. Here, we use telemetry data from 220 migratory Egyptian vultures Neophron percnopterus, tracked for 3, 186 bird months and across approximately 70% of the species' global distribution, to test for differences in survival throughout the annual cycle. We estimated monthly survival probability relative to migration and latitude using a multi‐event capture–recapture model in a Bayesian framework that accounted for age, origin, subpopulation and the uncertainty of classifying fates from tracking data. We found lower survival during migration compared to stationary periods ( β = −0.816; 95% credible interval: −1.290 to −0.318) and higher survival on non‐breeding grounds at southern latitudes (<25°N; β = 0.664; 0.076–1.319) compared to on breeding grounds. Survival was also higher for individuals originating from Western Europe ( β = 0.664; 0.110–1.330) as compared to further east in Europe and Asia, and improved with age ( β = 0.030; 0.020–0.042). Anthropogenic mortalities accounted for half of the mortalities with a known cause and occurred mainly in northern latitudes. Many juveniles drowned in the Mediterranean Sea on their first autumn migration while there were few confirmed mortalities in the Sahara Desert, indicating that migration barriers are likely species‐specific. Our study advances the understanding of important fitness trade‐offs associated with long‐distance migration. We conclude that there is lower survival associated with migration, but that this may be offset by higher non‐breeding survival at lower latitudes. We found more human‐caused mortality farther north, and suggest that increasing anthropogenic mortality could disrupt the delicate migration trade‐off balance. Research to investigate further potential benefits of migration (e.g. differential productivity across latitudes) could clarify how migration evolved and how migrants may persist in a rapidly changing world. Abstract : In a large tracking study of an endangered migratory bird, the authors found lower survival during migration compared to stationary periods and higher survival on non‐breeding as compared to on breeding grounds. They conclude that the cost associated with migration could be offset by higher non‐breeding survival at lower latitudes. The photo is by Kayahan Ağırkaya, KuzeyDoğa.